A MODEL FOR THE BASIC HELIX- LOOPHELIX MOTIF AND ITS SEQUENCE SPECIFIC RECOGNITION OF DNA (Journal of Sciences, Islamic Republic of Iran)
A three dimensional model of the basic Helix-Loop-Helix motif and its sequence specific recognition of DNA is described. The basic-helix I is modeled as a continuous ?-helix because no ?-helix breaking residue is found between the basic region and the first helix. When the basic region of the two peptide monomers are aligned in the successive major groove of the cognate DNA, the hydrophobic side chains of the helix I-helix I come in van der Waals proximity. In this way, the end residues of the helix I-helix I are placed far from each other so that a "loop" is needed to bring the helix II-helix II close together for hydrophobic interactions and therefore dimerization. The proposed sequence specific recognition is by hydrogen bonding of the conserved Asn (or Thr) and Glu side chains to the consensus guanine and adenine respectively. The methyl group of Thr and the hydrophobic residue next to it also produce a hydrophobic pocket for recognition of the methyl group of the consensus thymine. The highly conserved Arg's interact with backbone phosphates and a direct recognition of base pairs by Arg's is not likely